2018
DOI: 10.24329/jurkom.v1i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Pergeseran Peran Dan Fungsi Radio Suara Surabaya Dari Radio Informasi Menjadi Radio Pengaduan

Abstract: This study aims to identify factors causing the shift function of Radio Suara Surabaya. This research also explains the reason for the shift to occur. In examining the shift of Radio Suara Surabaya function from its original function and why the shift occurred, the researcher uses a qualitative research approach with descriptive research type. In the early stages of this study, the researchers identified the initial function of the establishment of Radio Suara Surabaya as an information radio. Furthermore, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…We found from previous research that instead of being a medium of information and radio journalism, SSFM shifted its function as a medium for public complaints (Sampoerno et al, 2018).…”
Section: Emotionmentioning
confidence: 80%
See 1 more Smart Citation
“…We found from previous research that instead of being a medium of information and radio journalism, SSFM shifted its function as a medium for public complaints (Sampoerno et al, 2018).…”
Section: Emotionmentioning
confidence: 80%
“…It's just that another study found that in terms of characters that are considered to reflect the public interest and the similarity of the characters of Surabaya residents, SSFM radio journalism has actually changed its function into a place for public complaints about bureaucratic services or public services (Sampoerno et al, 2018). Of course, to prevent this from happening, it is a big challenge for the radio itself to remain consistent in maintaining its face and personality as a friend of the citizens of Surabaya, not changing its function as customer service.…”
Section: Personalitymentioning
confidence: 99%
“…Radio dapat menjadi teman sembari mengerjakan tugas-tugas di rumah atau bisa juga ketika kita sedang bersantai. Radio juga salah satu media massa yang harganya relatif terjangkau untuk dibeli oleh masyarakat (Sampoerno et al, 2018). Radio pun memiliki kemampuan untuk berinteraksi secara langsung dengan pendengarnya (Astuti & Aritonang, 2019 Pada pengabdian masyarakat kali ini, penulis mengambil tema tentang konsep diri.…”
Section: A Pendahuluanunclassified